2001
DOI: 10.1073/pnas.221467098
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in aldosterone synthase predicts plasma glucose levels

Abstract: The mineralocorticoid hormone, aldosterone, is known to play a role in sodium homeostasis. We serendipitously found, however, highly significant association between single-nucleotide polymorphisms in the aldosterone synthase gene and plasma glucose levels in a large population of Chinese and Japanese origin. Two polymorphisms-one in the putative promoter (T-344C) and another resulting in a lysine͞arginine substitution at amino acid 173, which are in complete linkage disequilibrium in this population-were assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 44 publications
1
47
0
Order By: Relevance
“…The most studied polymorphism of CYP11B2 is T‐344C in the promoter region and the polymorphism is associated with higher aldosterone levels 23, 24. In a large population of individuals of Chinese and Japanese ancestry, CYP11B2 polymorphisms (Arg‐173 and T‐344C) were associated with higher FPG levels, higher 2‐hour post load glucose, impaired fasting glucose and type 2 diabetes mellitus,25 which is consistent with our findings of a high risk of type 2 diabetes mellitus in Chinese Americans with higher levels of aldosterone. Additionally, a prospective Japanese cohort study with 10 years of follow‐up demonstrated that plasma aldosterone levels predict the development of insulin resistance,26 suggesting our findings might extend to individuals with ancestry from the continent of Asia.…”
Section: Discussionmentioning
confidence: 99%
“…The most studied polymorphism of CYP11B2 is T‐344C in the promoter region and the polymorphism is associated with higher aldosterone levels 23, 24. In a large population of individuals of Chinese and Japanese ancestry, CYP11B2 polymorphisms (Arg‐173 and T‐344C) were associated with higher FPG levels, higher 2‐hour post load glucose, impaired fasting glucose and type 2 diabetes mellitus,25 which is consistent with our findings of a high risk of type 2 diabetes mellitus in Chinese Americans with higher levels of aldosterone. Additionally, a prospective Japanese cohort study with 10 years of follow‐up demonstrated that plasma aldosterone levels predict the development of insulin resistance,26 suggesting our findings might extend to individuals with ancestry from the continent of Asia.…”
Section: Discussionmentioning
confidence: 99%
“…19 Indeed, it is possible that the most common polymorphisms of the renin-angiotensin-aldosterone system studied so far have very little effect (if any) on BP and its consequences, as also suggested by our results 6 and those of another recent study. 20 Studies that analysed older populations (affected sibships, cross-sectional, and case-control studies) produced widely contradictory data 2,3 even if, overall, the T(À344) allele appears to be the 'unfavourable' one. 3 Population biases (criteria used to select patients and controls or differences in age, environmental, and ethnic/genetic background), lack of statistical power, epistatic interactions, 13,14 and, finally, publication bias toward positive association have been indicated as possible causes of these contradictory results.…”
Section: Discussionmentioning
confidence: 99%
“…The details of recruitment, exclusion criteria, phenotyping and genotyping have been described elsewhere [17,20,21]. In brief, the study was composed of concordant siblings (all siblings with hypertension) and discordant siblings (at least one hypertensive sibling).…”
Section: Methodsmentioning
confidence: 99%
“…Blood samples were taken for plasma glucose and insulin 1 and 2 h after glucose loading. The patients were not allowed to eat or drink until the end of the test [21].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation